Research on the Construction of Courses of Automotive Electronics and Electrical Appliances Based on the Joint Training Mode of Vocational Schools and Applied Undergraduate Courses - Wei Dan; Ren Xian; Ma Qi Hua (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
With the development of science and technology, automobile technology is increasingly improving in the direction of safety, environmental protection, and energy conservation. Automobile has been transformed from traditional mechanical products into typical mechatronics products. The role of automotive electronic and electrical technology in the production and use of automobiles has become more apparent. Automotive electronics and electrical courses are core courses in the vocational and applied undergraduate joint training model. This paper analyzes the current situation of the course, and puts forward the content of the course construction of automotive electronics and electrical appliances that is suitable for the joint training mode, which has certain guiding significance for the follow-up professional courses.